Importance of Antirabies Revaccination for an Adequate Antirabies Protection in Bovine Newborns - Filho, O. A. [UNESP]; Megid, Jane [UNESP]; Geronutti, L. [UNESP]; Ratti, J. [UNESP]; Kataoka, A. P. A. G.; Martorelli, L. F. A. (Amer Soc Microbiology, 2010)
The transfer of antirabies immunoglobulins in cows that were prime vaccinated and cows that were revaccinated against rabies correlated to the serum titers in their offspring was evaluated. The results demonstrated that revaccination against rabies during pregnancy induces neutralizing antibody titers at a protective level that are transferred directly to calves through colostrum and reinforce the importance of revaccination for improved colostral antibody transfer and offspring protection against rabies.